Fiqhi Lintas Agama dalam Paradigma Sosiologi Kontemporer - Husain Insawan (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Attendance of paradigm thinks fiqhi which have coronets “Fiqhi Cross Religion” have time to make sensationally [of] world “Perfiqhian” national because the attendance of assumed less inveterate in context of Indonesian Indonesia society and is known as the society of fiqhi. Paradigm appearance of fiqhi like this not quite of [of] situation think Indonesia society, especially some of conservative Moslem intelligentsias which comprehend and operate on the problem of contemporary people by using scalpel of fiqhi classic. This fact is real of him are a form of justice emasculating and to a potency of fiqhi able to grow and expand along a change of epoch which cannot avoid, at the same time [reply/answer] him without reducing values of tension Islam teaching stemming and al-Qur’an of al-Hadis. The paradigm of fiqhi cross religions at least wishes “playing at” at this region tried re-tracing kaleidoscope of fiqhi classic and also al-Qur’an nash-nash and of al-Hadis, later; then seat problem of people which emerge by proportional and give a solution of a problem of people. But this idea which loaded and publicized in the book which has them to of fiqhi cross Religion: Developing Society of Inklusif Pluralis written by Nurcholish Madjid have got a hard reaction and hot criticism of circle of traditional-conservative, though by dozens supporting the idea. This article tries to see a number of the reactions and him of in perpective of sociologist by using conflict theory and structural-functional.